The Cambridge handbook of shareholder engagement and voting - Kaur, Harpreet (Cambridge : Cambridge University Press, 2022)
All over the world, companies play an important role in the economy. Different types of stakeholders hold the reins in these companies. An important class are the shareholders that finance the activities of these companies. In return, stakeholders have a say on how these companies should be organized and structure their activities. This is primarily done through voting and engaging. These mechanisms of voting and engaging allow the shareholders to decide significant aspects of the company structure, from who governs it to how much directors are paid. However, how shareholders vote and engage and how far their rights stretch are organized differently in different countries. This pioneering book provides insights into what rights these shareholders have and how the shareholders of companies in nineteen different jurisdictions participate in corporate life through voting and engaging. Comparative and international in scope, it pays particular attention to how jurisdictions align and differ around the world.
Title from publisher's bibliographic system (viewed on 12 Sep 2022).
Keywords: Stockholders' voting; Stockholders; Corporations -- Investor relations .